Evaluation of impact of educational modules in improving the adverse drug reaction reporting from MBBS students - Sachidananda Adiga MN; G. Sivagnanam (Al Ameen Medical College, 2016)
Objective: To evaluate the impact of various educational modules implemented for second year MBBS students in their participation and reporting of ADRs to ADR Monitoring Centre (AMC). Background: To create awareness in students about importance of ADRs and their recognition as they are associated with high degree of morbidity and mortality. Medical council of India has made it mandatory that each medical college in India should have functioning pharmacovigilance program so that voluntary reporting of adverse drug reactions (ADRs) can be enhanced. Method: We have implemented clinical vignettes on ADR exercises in the practical curriculum. ADR crossword and ADR Photognosis competitions being the two optional modules conducted at the end of each four system to 2nd MBBS pharmacology students (120 students of 2012-13 batch MBBS students). Impacts of implementation of these modules were evaluated by objective and subjective yardsticks. Results: There has been extremely significant (p<0.005) increase in reporting of ADRs from attached teaching hospital were these students are posted for clinical training when compared to those students who were not exposed (Student's t- test). It has also been found that there was statistically significant increase in student participation as well as percentage of correct responses to ACEM and APCM exercises (Student's t -test). Conclusions: We conclude that by introducing educational programs in their curriculum, we can enhance their knowledge on ADR monitoring and reporting from teaching hospitals.